Homebound Happiness? Teleworkability of Jobs and Emotional Well-Being During Labor and Non-labor Activities - Juliane Hennecke; Andreas Knabe (Institute of Labor Economics (IZA), 2025)
This paper examines the relationship between flexible working arrangements (FWA) and workers' affective well-being (AWB), using data from the American Time-Use Survey (ATUS) and the Occupational Information Network (O*NET). We analyze differences in workers' emotional experiences during paid work, unpaid work, and leisure depending on the general availability of FWA within their occupation. Our findings reveal a significant negative association between teleworkability and AWB during labor activities for women, resulting in reduced day-average emotional well-being if jobs are also time-flexible. In contrast, we do not find significant associations between FWA and AWB during paid work for men. Additionally, we find no evidence of systematic spillovers to the AWB in non-labor activities for both men and women. Further nuanced findings regarding parents and the role of time flexibility underscore potential gender differences in the impact of FWA on well-being.
Keywords: J22; J81; D91; I31; 330; flexible working arrangements; affective well-being; telework; working from home; work and family; work-life balance; gender differences